2023
DOI: 10.1111/1750-3841.16489
|View full text |Cite
|
Sign up to set email alerts
|

Application of chickpea‐based edible coating with chickpea husk polyphenols on the preservation of sunflower seeds

Abstract: The objective of this study was to evaluate the protective effect of a chickpea-based edible coating with the addition of polyphenols on the chemical, microbiological, and sensory quality of roasted sunflower seeds throughout storage. Four different samples were prepared: roasted sunflower seeds (control sample, SF-C), roasted sunflower seeds with BHT (SF-BHT), roasted sunflower seeds with chickpea-based coating (SF-CCs), and roasted sunflower seeds with chickpea-based coating with chickpea polyphenolic extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
2
5
0
Order By: Relevance
“…This behavior was also observed in the investigation carried out by Camiletti et al. (2023) in sunflower seeds coated with a chickpea flour edible coating loaded with chickpea polyphenols.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…This behavior was also observed in the investigation carried out by Camiletti et al. (2023) in sunflower seeds coated with a chickpea flour edible coating loaded with chickpea polyphenols.…”
Section: Resultssupporting
confidence: 78%
“…Similarly, Camiletti et al. (2023) found that sunflower seeds coated with a chickpea flour edible coating exhibited low levels of total mesophilic microorganisms (<230 CFU/g) and molds and yeasts (<10 CFU/g) after 60 days of storage, indicating negligible growth of these microorganisms. Considering the aforementioned, it is worthwhile to conduct further investigations into the potential antimicrobial effects of microencapsulated peanut skin polyphenols incorporated into food matrices with elevated water activity and moisture content.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of pH, plasticizer (glycerol) concentration, and the addition of an antioxidant (gallic acid) on film properties have been investigated [ 3 , 4 ]. There has been research into the preservation capability of sunflower oil and seeds in chickpea flour films [ 5 , 6 ]. In addition, films based on chickpea flour and chitosan or polyethylene oxide added to curcumin [ 7 , 8 ] have been studied.…”
Section: Introductionmentioning
confidence: 99%